Factors Associated with Caregivers' Concern in Maintaining the Oral Function of Elderly Living in Long-Term Care Facilities - Nugraha, Susiana; Rahardjo, Tri Budi Wahyuni; Higashijima, Misako; Hirano, Yuko (UI Scholars Hub, 2025)
This study investigated the attentiveness of elderly caregivers in long-term care facilities in maintaining oral function. A cross-sectional approach was used to achieve the study's purpose. The sample size formula accounted for 213 caregivers randomly selected from 18 long-term care facilities in 4 provinces. A self-reported questionnaire of sociodemographic characteristics and an adapted Leopold’s oral care checklist was distributed. The average age of study participants was 35.24 (±11.2 SD; aged 18–70 years), dominated by females (62.9%), and only 39% had experienced long-term care training. Multiple linear regression analysis indicated that younger caregivers likely pay more attention in the swallowing periods (β = -.182), females pay more attention in meal preparation (β = .146), and environmental observation (β = -. 238). Caregivers working in public long-term care facilities and having longer working experience paid more attention in environmental observation (β = .172) and (β = -.161), while training experience showed a significant association with feeding and swallowing periods (β = .291) and (β = .211). This study highlights the importance of training programs for care capacity, particularly oral care.